Pengaruh Gaya Kepemimpinan, Budaya Organisasi, Dan Komitmen Organisasi Terhadap Kinerja Karyawan (Studi Pada PT. Niramas Pandaan Sejahtera) - NUR AINI; Abd kodir Djaelani; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis research was conducted at a branch company of PT. Niramas Pandaan Sejahtera Pasuruan Regency. The purpose of this study was to examine and analyze the influence of leadership style, organizational culture and organizational commitment on the performance of the branch employees of PT. Niramas Pandaan Sejahtera, Pasuruan Regency, East Java 67156. The population in this study were all employees of the branch of PT. Niramas Pandaan Sejahtera, totaling 65 employees. The sampling technique in this study used saturated samples. And the analysis used includes instrument testing, normality test, multiple regression analysis, classical assumption test, and hypothesis testing.         The results showed that the variable organizational culture and organizational commitment did not have a significant effect on the performance of the branch employees of PT. Niramas Pandaan Sejahtera Pasuruan Regency, while the variable of leadership style has a significant effect on the performance of the branch employees of PT. Niramas Pandaan Sejahtera. Keywords: leadership style, organizational culture and organizational commitment and    employee performance